Methods And Technologies For Developing Reflective Skills (Trainings, Interactive Methods, Game Technologies) - Omanova, Nuriya Shukhrat qizi (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
This article analyzes the methods and technologies used in developing reflective skills among future educators and caregivers. Specifically, reflection is considered as a means for analyzing one’s activities, self-awareness, and achieving professional growth. The study examines the impact of training sessions, interactive methods (such as discussions, clustering, concept mapping, and brainstorming), as well as game technologies on reflective processes. Additionally, the compatibility of innovative pedagogical technologies with reflective education and the mechanisms for their implementation in practice are substantiated.